Study and Applying of Search Engine Technique in Mobile Internet Music - Yiping Yang; Yuzhong Zhang; Haojie Yang; Pingbo Song (Dianxin kexue)
The music business of China Telecom have high performance, more reasonable precision ratio and recall ratio, timeliness of indexing and other needs in music search to meet the requirements for mobile internet users. The search engine technology for applications in the field of music search was explored and a solution of music search for the mobile internet users was put forward. The hierarchy searching strategies improve the flexibility of the search engine when combining it's searching rules. The indexing mechanism which implements by integrating the memory index and the file index ensures to present music in time.